Nonlocal Boundary Value Problems for q-Difference Equations and Inclusions - Sotiris K. Ntouyas; Jessada Tariboon (International Journal of Differential Equations)
We study boundary value problems for q-difference equations and inclusions with nonlocal and integral boundary conditions which have different quantum numbers. Some new existence and uniqueness results are obtained by using fixed point theorems. Examples are given to illustrate the results.